Impacts of Construction and Demolition Waste on Environment: An Overview - Haradhan Kumar Mohajan (Studies in Social Science & Humanities, 2025)
Construction and demolition (C&D) wastes are the generated materials as wastes comprising of building materials, debris and rubble resulting from construction, remodeling, repair, and deconstruction of any civil structure that is about 40% of all the solid wastes. The global C&D sector is low resource efficiency that leads to a significant waste generation area. The C&D wastes are soils, tiles, concrete, bricks, plaster, rubble, glass, wood, asphalt, plasterboard, asbestos, plumbing fixtures, metals, plastics, stone, wall paper, etc.; and these are heavy and dense, necessitating more storage space and cannot be managed easily. These must be handled properly during collection, procession, recover, recycle, and disposal. These are increasing for the construction of various new infrastructures and for the deconstruction of old or small structures due to urbanization, industrialization, economic development, and rapid population growth. Increase of C&D waste is creating harmful effects on the environment, ecological resources, and human life. The aim of this explorative study is to reduce dependence on virgin construction materials and promote resource efficiency through waste reduction, reuse, and recycling.